Millennials’ acceptability of tawarruq-based ar-rahnu in Malaysia - Hanudin Amin; M. Kabir Hassan (Emerald Group Publishing Ltd., 2022)
This study aims to enlighten the effects of Islamic religiosity, Islamic altruism and Islamic debt collection policy (IDCP) on millennials’ acceptability of tawarruq-based ar-rahnu in Malaysia. This study applies the factors drawn from the Islamic theory of consumer behaviour (ITCB) and uses data obtained from a survey of 267 respondents to examine the impact of these factors on millennials’ acceptability of tawarruq-based ar-rahnu. The findings indicate that Islamic religiosity, Islamic altruism and IDCP are all important factors influencing millennials’ acceptability of tawarruq-based ar-rahnu. The study is narrowed down in scope in terms of the broader context of tawarruq-based ar-rahnu and the variables retrieved from the ITCB, which may explain its limited impact. Considering the effects of the variables investigated in this study might assist enhance product acceptance among consumers. This study is focussed on tawarruq-based ar-rahnu in the context of the ITCB, taking a different approach than past research on the subject.